2019
DOI: 10.1080/17429145.2019.1689582
|View full text |Cite
|
Sign up to set email alerts
|

A tomato and tall fescue intercropping system controls tomato stem rot

Abstract: Intercropping can effectively control some plant soil-borne diseases. However, few studies on intercropping have focused on forage grass as companion plants. In this experiment, Festuca arundinacea (tall fescue) was selected as the intercropping forage to explore whether it could control tomato stem rot. We found that: (1) tomato intercropped with tall fescue had a significantly lower disease incidence and disease index of tomato stem rot than sole tomato; (2) the antifungal activities of the root exudates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…We found that the absolute abundance of Proteobacteria, Nitrososphaera, Bacillus , and Actinobacteria was significantly higher, while that of Candidatus_Koribacter was significantly lower in intercropping pattern. Taking the above results into consideration, the positive change in soil prosperity and the assumption that the intercropping may be capable of improving the resistance of litchi root systems to soil-borne diseases are consistent with previously reported findings (Morris et al, 2017 ; Zhou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the absolute abundance of Proteobacteria, Nitrososphaera, Bacillus , and Actinobacteria was significantly higher, while that of Candidatus_Koribacter was significantly lower in intercropping pattern. Taking the above results into consideration, the positive change in soil prosperity and the assumption that the intercropping may be capable of improving the resistance of litchi root systems to soil-borne diseases are consistent with previously reported findings (Morris et al, 2017 ; Zhou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Plant–plant communication can be maximized by managed intercropping to locate aboveground and below‐ground plant parts in close proximity to chemicals released by neighbour plants, which can directly inhibit the germination and growth of pathogenic fungi and bacteria or repel herbivores from fields (Lazazzara et al, 2018; Quintana‐Rodriguez et al, 2015; Yang et al, 2014; Zhou, Cen, Tian, Wang, & Zhang, 2019). Volatiles from resistant cultivars contain volatiles that can directly inhibit pathogen growth or induce systemic resistance in neighbour susceptible cultivars (Lazazzara et al, 2018; Quintana‐Rodriguez et al, 2015).…”
Section: Wireless Communication: Signal Input‐transfer‐output Modelmentioning
confidence: 99%
“…Intercropped plants can emit infochemicals that alter the transcriptomes of neighbouring plants to cope with pathogens. RNA‐seq results suggest that tall fescue root exudate containing putrescine and cyclohexane‐1,2‐diol stimulates the expression of genes related to defence hormones and pathogenesis‐related proteins in tomato, and reduces stem rot disease (Zhou et al, 2019).…”
Section: Wireless Communication: Signal Input‐transfer‐output Modelmentioning
confidence: 99%
“…Plant-plant communication can be maximized by managed intercropping to locate aboveground and belowground plant parts in close proximity to chemicals released by neighbor plants, which can directly inhibit the germination and growth of pathogenic fungi and bacteria or repel herbivores from fields (Lazazzara et al , 2018, Quintana-Rodriguez et al , 2015, Yang, Zhang, Qi, Mei, Liao, Ding, Deng, Fan, He, Vivanco, Li, Zhu & Zhu, 2014, Zhou, Cen, Tian, Wang & Zhang, 2019. Volatiles from resistant cultivars contain volatiles that can directly inhibit pathogen growth or induce systemic resistance in neighbor susceptible cultivars (Lazazzara et al , 2018, Quintana-Rodriguez et al , 2015.…”
Section: ? Field Applicationsmentioning
confidence: 99%
“…Intercropped plants can emit infochemicals that alter the transcriptomes of neighboring plants to cope with pathogens. RNA-seq results suggest that tall fescue root exudate containing putrescine and cyclohexane-1,2-diol stimulates the expression of genes related to defense hormones and pathogenesis-related proteins in tomato, and reduces stem rot disease (Zhou et al , 2019).…”
Section: ? Field Applicationsmentioning
confidence: 99%